Impacts of Polycystic Ovary Syndrome (PCOS) on cutaneous manifestations and acne control I, II, III: Clinical case (Research, Society and Development, 2025)
Acne is a chronic inflammatory condition affecting the pilosebaceous unit and presents with varying degrees of severity, ranging from mild comedonal forms to deep nodulocystic lesions. Polycystic Ovary Syndrome (PCOS), characterized by hyperandrogenism, menstrual irregularity, and the presence of ovarian cysts, is one of the main causes of persistent acne in young women. The objective of this study was to describe and analyze the clinical evolution of a patient with acne vulgaris associated with PCOS, highlighting the importance of a multidisciplinary approach including medical, nutritional, and aesthetic factors in controlling skin manifestations and promoting quality of life. This is a descriptive and retrospective clinical case study, conducted between September 2024 and July 2025, involving a 20-year-old female patient diagnosed with PCOS and acne grades I, II, and III. The results demonstrated that after ten months, there was remission of grade III inflammatory lesions, with only isolated comedones and slight post-inflammatory hyperpigmentation remaining. Hormonal stabilization was essential for controlling dermatological manifestations, while aesthetic interventions favored tissue regeneration and scar prevention. It is concluded that acne associated with PCOS requires an interdisciplinary and continuous approach, involving hormonal regulation, nutritional support, and aesthetic follow-up. The patient reported a noticeable improvement in self-esteem, well-being, and social integration.